CD40 Ligand/Trimer DNA Enhances Both Humoral and Cellular Immune Responses and Induces Protective Immunity to Infectious and Tumor Challenge - Gurunathan, Sanjay (1998)
CD40/CD40 ligand interactions have a central role in the induction of both humoral and cellular immunity. In this study, we examined whether a plasmid expressing CD40 ligand/trimer (CD40LT) could enhance immune responses in vivo. BALB/c mice were injected with plasmid expressing β-galactosidase DNA with or without CD40LT DNA or IL-12 DNA, and immune responses were assessed. Mice vaccinated with β-gal DNA plus CD40LT DNA or IL-12 DNA had a striking increase in Ag-specific production of IFN-γ, cytolytic T cell activity, and IgG2a Ab. The mechanism by which CD40LT DNA enhanced these responses was further assessed by treating vaccinated mice with anti-IL-12 mAb or CTLA-4 Ig (CTLA4Ig). Production of IFN-γ and CTL activity was abrogated by these treatments, suggesting that CD40LT DNA was mediating its effects on IFN-γ and CTL activity through induction of IL-12 and enhancement of B7 expression, respectively. Physiologic relevance for the ability of CD40LT DNA to enhance immune responses by the aforementioned pathways was shown in two in vivo models. First, with regard to CTL activity, mice vaccinated with CD40LT DNA did not develop metastatic tumor following challenge with lethal dose of tumor. Moreover, in a mouse model requiring IL-12-dependent production of IFN-γ, mice vaccinated with soluble Leishmania Ag and CD40LT DNA were able to control infection with Leishmania major. These data suggest that CD40LT DNA could be a useful vaccine adjuvant for diseases requiring cellular and/or humoral immunity.